Variations in very preterm birth rates in 30 high‐income countries: are valid international comparisons possible using routine data?. (10th September 2016) - Delnord, M; Hindori‐Mohangoo, AD; Smith, LK; Szamotulska, K; Richards, JL; Deb‐Rinker, P; Rouleau, J; Velebil, P; Zile, I; Sakkeus, L; Gissler, M; Morisaki, N; et al.
Abstract : Objective: Concerns about differences in registration practices across countries have limited the use of routine data for international very preterm birth (VPT) rate comparisons. Design: Population‐based study. Setting: Twenty‐seven European countries, the United States, Canada and Japan in 2010. Population: A total of 9 376 252 singleton births. Method: We requested aggregated gestational age data on live births, stillbirths and terminations of pregnancy (TOP) before 32 weeks of gestation, and information on registration practices for these births. We compared VPT rates and assessed the impact of births at 22–23 weeks of gestation, and different criteria for inclusion of stillbirths and TOP on country rates and rankings. Main outcome measures: Singleton very preterm birth rate, defined as singleton stillbirths and live births before 32 completed weeks of gestation per 1000 total births, excluding TOP if identifiable in the data source. Results: Rates varied from 5.7 to 15.7 per 1000 total births and 4.0 to 11.9 per 1000 live births. Country registration practices were related to percentage of births at 22–23 weeks of gestation (between 1% and 23% of very preterm births) and stillbirths (between 6% and 40% of very preterm births). After excluding births at 22–23 weeks, rate variations remained high and with a few exceptions, country rankings were unchanged. Conclusions: International comparisons of very preterm birth rates using routine data should exclude births at 22–23 weeks of gestation and terminations of pregnancy. The persistent large rate variations after these exclusions warrant continued surveillance of VPT rates at 24 weeks and over in high‐income countries. Tweetable abstract: International comparisons of VPT rates should exclude births at 22–23 weeks of gestation and terminations of pregnancy. Tweetable abstract: International comparisons of VPT rates should exclude births at 22–23 weeks of gestation and terminations of pregnancy.